Surface polariton excitation in ZnO films deposited using ALD - Venger, E.F.; Melnichuk, L.Yu.; Melnichuk, A.V.; Semikina, T.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The conductive ZnO films deposited using atomic layer deposition (ALD) on the optical glass substrates were studied using the modified method of the disturbed total internal reflection within the range 400…1400 cm⁻¹ for the first time. The frequency “windows” with the obtained excited surface phonon and plasmon-phonon polaritons have been found in the measured infrared reflectance spectra. The dispersion response of high and low frequency branches of the IR spectra have been presented.